2010
DOI: 10.1007/s00404-010-1548-4
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin SNP45TG is associated with gestational diabetes mellitus

Abstract: We concluded that SNP45TG in adiponectin gene is associated with the occurrence of GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 30 publications
4
46
1
1
Order By: Relevance
“…Earlier studies have reported the significant association of the SNPs GCK (rs1799884 and rs4607517), IGF2BP2 (rs4402960), KCNJ11 (rs5219), MTNR1A (rs2119882), MTNR1B (rs1387153 and rs10830963), SRR (rs391300), and TCF7L2 (rs12255372) with GDM in whites and Asians, mainly Koreans, Chinese, and Malayasians. 4,[16][17][18][19][20] The TCF7L2 gene SNP rs12255372 showed only a moderate significant association (P = 0.054) with GDM in the present study, although this SNP has previously shown association with T2DM in Asian Indians. 30 The association of rs12255372 with GDM has been reported in other populations like Mexican Americans, whites, and Koreans.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Earlier studies have reported the significant association of the SNPs GCK (rs1799884 and rs4607517), IGF2BP2 (rs4402960), KCNJ11 (rs5219), MTNR1A (rs2119882), MTNR1B (rs1387153 and rs10830963), SRR (rs391300), and TCF7L2 (rs12255372) with GDM in whites and Asians, mainly Koreans, Chinese, and Malayasians. 4,[16][17][18][19][20] The TCF7L2 gene SNP rs12255372 showed only a moderate significant association (P = 0.054) with GDM in the present study, although this SNP has previously shown association with T2DM in Asian Indians. 30 The association of rs12255372 with GDM has been reported in other populations like Mexican Americans, whites, and Koreans.…”
Section: Discussioncontrasting
confidence: 76%
“…Recent studies have shown that the T2DM-associated gene variants were also found to be associated with GDM susceptibility. 4,[16][17][18][19][20] Among the genes that were investigated in the present study, CDKAL1 is the only gene that showed association with GDM in our south Indian population. Both SNPs of the CDKAL1 gene-rs7754840 and rs7756992-showed association with GDM even after Bonferroni's correction with a power of 61% and 82%, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…G allele of rs2241766 is signifi cantly more frequent in women with GDM (32.7%) than those with normal glucose (17.9%, p ϭ .038) in Malaysians (Low et al, 2010). Similar to prior work (Ranheim et al, 2004), Low and colleagues (2010) also reported a significantly lower plasma adiponectin level during early pregnancy in women with GDM than those without ( p Ͻ .05).…”
Section: Genes Affecting Insulin Resistance Function Adipoqsupporting
confidence: 68%
“…These genes have also been studied in women with GDM of various races, including Americans, Europeans, Mediterraneans, Asians, and Arabians. The number of women with GDM included in these studies ranged greatly from 25 (Low, Mohd Tohit, Chong, & Idris, 2010) to 930 (Shin et al, 2010). Sample size powered at least 80% was reported in only 6 of 24 studies (King, 2007;Lauenborg et al, 2009;Pappa et al, 2011;Shaat et al, 2005;Zhou et al, 2009).…”
Section: Resultsmentioning
confidence: 97%